A estimulação da consciência fonológica e sua repercussão no processo de aprendizagem da lecto-escrita - Basso, Fabiane Puntel (2006)
This research aims to understand the repercussion in children's lecto-writing performance caused by the metaphonological pre-alphabetic stimulation. The children were stimulated in the Kindergarten and were analysed in the 1st year of the Elementary School. The studies were realized in an Elementary Public School, which integrates the Teaching Municipal System in Santa Maria-RS. wenty children from two first year classes have participated in the research. They were divided into 4 groups: D, E, F and G. Ten children participated in the metaphonological activities in the Kindergarten (groups D and E) and 10 children did not participate in these activities (groups F and G). Different activities were realized in order to understand the children advances. These include tests of Phonological Awareness, Reading, Writing, Writing and Orthographic Exploration, and Reader Comprehension. The results of these tests shows that the phonological awareness stimulation in the Kindergarten Education causes a difference in the performance of the lecto-writing just in children from the group E. This conclusion was possible because of the comparison between children from the groups E and F. In this comparison, the children of group E have superior performance in all activities. Children from the groups D and G demonstrate similar performances in the activities involving the lecto-writing. The stimulation of the phonological awareness seems to have benefited the children in group E, by influencing the social functions of the writing language and its relationship with the oral language. These benefits did not happen to the children of the group D. The use of pedagogical strategies organized by the teachers, involving the relationship between the phonological awareness and the lecto-writing, can facilitate the process of comprehension of the alphabetic system. In this way, the relationships among the phonological awareness, the lecto-writing, orthographic writing and text comprehension can be used with pedagogical purposes, if the teachers take into account the previous experiences from children who enter in the elementary school. It is important that teachers be aware of the school function to children that start their studies without having the opportunity to live in a good environment, with reading and writing stimulation.